The role of SES in Chinese (L1) and English (L2) word reading in Chinese‐speaking kindergarteners. (12th March 2015) - Liu, Duo; Chung, Kevin K. H.; McBride, Catherine
Abstract : The present study investigated the relationships between socioeconomic status (SES) and word reading in both Chinese (L1) and English (L2), with children's cognitive/linguistic skills considered as mediators and/or moderators. One hundred ninety‐nine Chinese kindergarteners in Hong Kong with diverse SES backgrounds participated in this study. SES explained unique variance in English word reading even after age, phonological processing, vocabulary and working memory were controlled. However, the effect of SES on Chinese word reading became nonsignificant when these control variables were included. Moreover, phonological awareness showed a full mediating effect on the relationship between SES and Chinese word reading. Both phonological awareness and vocabulary were found to partially mediate the association between SES and English word reading. These findings complement our understanding of the relation between SES and reading development in Chinese societies and may have policy or intervention development implications.